Appraisal And Perceptivity Of Proteins Purified From Zygogramma Bicolorata (Coleoptera: Chrysomelidae) Against Pathogens Engendering Mycotic Infection (Applied Biological Research, 2019)
The multidrug resistivity (MDR) of opportunistic microorganisms is still a major concern which requires the development of a new efficient drug with  fewer side effects that can be added to the antifungal armamentarium. This  study is the first to report the antifungal nature of proteins purified from  the hemolymph of Zygogramma bicolorata, immunized with Micrococcus  luteus (MTCC 106) and Escherichia coli (MTCC 443). Immunized  hemolymph was assayed for antimicrobial sensitivity against pathCandida albicans (ITCC 4718) and Aspergillus niger (ITdiffusion method. The crude extract of hemolymph was separated and  purified into fractions by low-pressure size exclusion chromatography using  a Sephadex G-25 column. Protein estimation for crude fraction was  performed by Lowry’s method followed by the assessment of antifungal  activity. The study revealed that four fractions (fraction 6, 9, 11 and 15) out  of 30 fractions exhibited activity against the test organisms and  accommodated high and low molecular weight proteins/peptides of 120, 100,  90 and 66 kDa and two relatively low molecular weight polypeptides (36 and  18 kDa) respectively. Being MDR in dire matter, the efficacy of the drug is  momentous.
Keywords: Antimicrobial peptides; Aspergillus niger; Candida albicans; hemolymph; SDS-PAGE